(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
Substitutional study of Zn on YBa\(_2\)Cu\(_3-x\)Zn\(_x\)O\(_7-δ\) \((0 < x < 0.1)\) have been carried out on polycrystalline samples to determine the effect of Zn doping in small concentration on the instability of the unit cell structure in the presence of water. YBa\(_2-x\)Sr\(_x\)Cu\(_3\)O\(_7-δ\) and YBa\(_2\)Cu\(_3-x\)Al\(_x\)O\(_7-δ\) polycrystalline samples for various concentration of Sr\((0 < x < 0.6)\) and Al\((0 < x < 0.6)\) have also been treated with water. The degree of degradation in the substituted samples is a function of the type of the dopant Sr\(^2+\)/Al\(^3+\)/Zn\(^2+\) as well as the molar concentration of the dopant. The degradation is found to be minimum in the case of Sr\(^2+\) substitution at Ba\(^2+\) sites in YBa\(_2\)Cu\(_3\)O\(_7-δ\) as compared to the degradation of Al\(^3+\) and Zn\(^2+\) substitution at Cu\((1)\) and Cu\((2)\) sites, respectively. The degradation is maximum in the case of Zn\(^2+\) substitution at Cu\((2)\) site. The studies were made using R-T measurements, X-ray diffraction technique and iodometric titration method and SEM.